Population pharmacokinetic–pharmacodynamic modelling of the relationship between testosterone and prostate specific antigen in patients with prostate cancer during treatment with leuprorelin. Issue 6 (3rd April 2019) - Snelder, Nelleke; Drenth, Henk‐Jan; Riber Bergmann, Kirsten; Wood, Nolan David; Hibberd, Mark; Scott, Graham
Abstract : Aims: This investigation aimed to quantitatively characterize the relationship between the gonadotropin‐releasing hormone agonist leuprorelin, testosterone (T) and prostate specific antigen (PSA) concentrations over time, to aid identification of a target T concentration that optimises the balance of the benefits of T suppression whilst reducing the risk of side effects related to futile over‐suppression. Methods: Data from a single dose study to investigate the effect of leuprorelin in a 6‐month depot formulation on T and PSA in prostate cancer patients were analysed using a population pharmacokinetic–pharmacodynamic modelling approach. The developed model was qualified using external data from 3 studies, in which the effect of different formulations of leuprorelin on T and PSA was evaluated in prostate cancer patients. Results: The effect of leuprorelin on the relationship between T and PSA was adequately characterized by the Romero model with minor modifications, combined with a turnover model to describe the delay in response between T and PSA. The data were significantly better described when assuming a minimum PSA level that is independent on the treatment‐related reduction in T, as compared to a model with a proportional reduction in PSA and T. Conclusions: The model‐based analysis suggests that on a population level, reducing T concentrations below 35 ng/dL does not result in a further decrease in PSA levels (>95% of the minimal PSA level is reached). More data are required to support this relationship in the lower T and PSA range.